To Evaluate the Different Divisions and Variations of The Coronary Arteries in The Cadaveric Human Heart - Devendra Kumar Sirohi (Asian Journal of Medical Research, 2016)
Background: Knowledge of anatomical changes in the coronary artery and its branches is essential for cardiac surgeons to improve imaging methods and perform coronary artery bypass grafting with greater precision. The corpse had several abnormalities of the coronary arteries upon detection. Aim: To evaluate the different divisions and Variations of the coronary arteries in the cadaveric human heart. Methodology: The research used adult cadavers of both genders (aged 23–68 years) to examine the hearts. The hearts were preserved using a 10% formaldehyde solution and were gathered specifically for this investigation. Approval was received from the Institutional Ethical Committee of the college. We obtained 80 human hearts from the preserved bodies of both males and females, which were stored in the Department of Anatomy, Venkateshwara IMS. The specimens were immersed in a solution of formaldehyde diluted to a concentration of 10%. The hearts were analysed according to the fundamental principles of anatomy. Results: 74 cases (92.5%) and 73 cases (91.25%), the PD branch and the branch to the AV node were identified as branches of the RCA, respectively. Both the branch to the SA node and the acute marginal branch were consistently identified as branches originating from the RCA in all patients. In this investigation, it was shown that in all 65 instances, the obtuse marginal artery originated from the circumflex coronary artery. In 6 instances (7.5% of the total) the presence of the posterior descending or posterior interventricular artery and the branch to the AV node was found. In 9 cases (11.25% of the total), the same arteries were also present. Therefore, in the current investigation, 74 out of 80 hearts (92.5%) exhibit right dominance. The left circumflex artery supplies the posterior interventricular septum in just 6 occurrences, accounting for 7.5% of the total. As a result, the heart is considered left dominant. Conclusion: A comprehensive understanding of the architecture of coronary arteries and their variations is essential for achieving favourable clinical outcomes in the treatment of coronary artery disorders.